Effects of metacognitive strategy instructions on reading comprehension and critical thinking skills of international undergraduate students - Babashamsi, Parastoo (2021)
Metacognitive strategies have been investigated as facilitating tools for students’ reading comprehension. Few studies have investigated the detailed procedure of systematically delivering and teaching metacognitive strategies in higher education. To fill the gap, the researcher aims to investigate whether explicit training in metacognitive strategies could improve undergraduates’ reading comprehension and critical thinking skills. Quasiexperimental design, repeated measure ANOVA, and semi-structured interviews were conducted with six students in an experimental metacognitive group to support the results of the quantitative data. The data were collected using the reading test, Cornell Critical thinking skill test, and Metacognitive Reading Awareness Strategy inventory. The experimental group and control group underwent 14 sessions of training. Apart from teaching metacognitive strategies to the experimental group, both groups were taught using similar teaching materials. Upon completing the treatment, post-tests of reading and critical thinking skills were administered to all participants. Semi-structured interviews and a Metacognitive Reading Awareness Strategy Assessment were conducted among experimental students. The results showed a statistically significant difference between the scores of students taught in metacognitive reading comprehension and the conventional group (F=2, 126) = 269.445. p <0.05). The results related to critical thinking tests revealed the mean scores of students in the metacognitive group were significantly higher than the mean score of the students in the conventional reading group (F= 1.3,82.3) = 215.973. p <0.001). The results of the Metacognitive Reading Awareness Strategy Assessment showed that students had more awareness of global reading strategies (M= 3.511), followed by supporting reading strategies (M=3.468) and problem-solving strategies (M= 3.427). The thematic analysis result supported that students were moderate users of planning and monitoring strategies while less frequently used evaluative strategies. The results also revealed that students perceived that lack of vocabulary knowledge, heavy dependence on their teachers, and lack of strategy training were the main causes of their reading difficulties. The findings implied that EFL teachers should introduce metacognitive reading strategies through appropriate and systematic instructions to enable the students to implement them in their academic reading.